Alteration in neuromuscular function of the plantar flexors following caffeine ingestion. Issue 1 (6th May 2014) - Behrens, Martin; Mau‐Moeller, Anett; Heise, Sandra; Skripitz, Ralf; Bader, Rainer; Bruhn, Sven
<x xml:space="preserve">Abstract</x> The aim of this study was to compare the neuromuscular function of the plantar flexors following caffeine or placebo administration. Thirteen subjects (25 ± 3 years) ingested caffeine or placebo in a randomized, controlled, counterbalanced, double‐blind crossover design. Neuromuscular tests were performed before and 1 h after caffeine or placebo intake. During neuromuscular testing, rate of torque development, isometric maximum voluntary torque, and neural drive to the muscles were measured. Triceps surae muscle activation was assessed by normalized root mean square of the EMG signal during the initial phase of contraction (0–100 ms, 100–200 ms) and maximal voluntary contraction (MVC). Furthermore, evoked spinal reflex responses of the soleus muscle (H‐reflex evoked at rest and during MVC, V‐wave) and peak twitch torques were evaluated. The isometric maximum voluntary torque and evoked potentials were not different. However, we found a significant difference between groups for rate of torque development in the time intervals 0–100 ms [41.1 N·m/s (95% CI: 8.3–73.9 N·m/s, P = 0.016)] and 100–200 ms [32.8 N·m/s (95% CI: 2.8–62.8 N·m/s, P = 0.034)]. These changes were accompanied by enhanced neural drive to the plantar flexors. Data suggest that caffeine solely increased explosive voluntary strength of the triceps surae because of enhanced neural activation at the onset of contraction whereas MVC strength was not affected.